On Cubic Interval Vague Sets and Cubic Interval Vague Topological Spaces - Haji, Arsalan Shareef; Khalaf, Alias Barakat (Science Journal of University of Zakho, 2022)
advance a modern extension formation of cubic vague sets identified as cubic interval vague sets (CIVSs). similarly describe the idea of cubic interval vague sets (ICIVSs) cubic interval vague sets (ECIVSs) by examples debate their exciting properties, excluding ICIVSs ECIVSs - . Additionally, show - ICIVSs ( ECIVSs) necessity not be an ICIVS (or ECIVS). apply the idea of (CIVS) to topological spaces and present the idea of cubic interval vague topological spaces. Further, we introduce P-cubic interval vague topological space and R-cubic interval vague topological space. We discuss basic properties of cubic interval vague topological space.